The Bioavailability, Biodistribution, and Toxic Effects of Silica-Coated Upconversion Nanoparticles in vivo - Zhou, Mingzhu; Ge, Xiaoqian; Ke, Da-Ming; Tang, Huan; Zhang, Jun-Zheng; Calvaresi, Matteo; Gao, Bin; Sun, Lining; Su, Qianqian; Wang, Haifang (Frontiers in Chemistry, 2019)
Lanthanide-doped upconversion nanoparticles can convert long wavelength excitation radiation to short wavelength emission. They have great potential in biomedical applications, such as bioimaging, biodetection, drug delivery and theranostics. However, there is little information available on their bioavailability and biological effects after oral administration. In this study, we systematically investigated the bioavailability, biodistribution, and toxicity of silica-coated upconversion nanoparticles administrated by gavage. Our results demonstrate that these nanoparticles can permeate intestinal barrier and enter blood circulation by microstructure observation of Peyer’s patch in the intestine. Comparing the bioavailability and the biodistribution of silica-coated upconversion nanoparticles with oral and intravenous administration routes, we found that the bioavailability and biodistribution are particularly depended on the administration routes. After consecutive gavage for 14 days, the body weight, pathology, Zn and Cu level, serum biochemical analysis, oxidative stress, and inflammatory cytokines were studied to further evaluate the potential toxicity of the silica-coated upconversion nanoparticles. The results suggest that these nanoparticles do not show overt toxicity in mice even at a high dose of 100 mg/kg body weight.